Teacher Educators’ Apprenticeships of Observation and Community-Based Field Settings - Taylor, Linda K.; Hamilton, Erica R.; Burns, Amy; Leonard, Alison E. (Frontiers in Education, 2022)
This paper presents findings from a two-year collaborative self-study examining four teacher educators’ experiences facilitating community-based field experiences in the United States and Canada. To examine our experiences working in these field settings we drew Experiential Learning Theory (ELT) as well as the concept of apprenticeship of observation. Facilitating preservice teachers’ learning in field settings outside traditional PK-12 contexts, such as museums and a construction site, prompted us to consider how apprenticeships of observation and ELT intersect when seeking to expand preservice teacher education to also include community-based field settings. Working in these community-based field settings also served to disrupt some of our own apprenticeships of observation. Finally, we noted that when working in these non-traditional field settings and utilizing the ELT framework, our experiences as teacher educators were neither sequential nor unidirectional.